Dinamika Konflik dan Integrasi Antara Etnis Dayak dan Etnis Madura (Studi Kasus di Yogyakarta Malang dan Sampit) - Khoiruddin Bashori; Abd Majid; Mahli Zainuddin Tago (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2012)
Indonesia is one of the most pluralistic societies in the world consisting of various social groups, ethnics, tribes, languages and religious diversities. However, the social, political, and cultural diversities among people have frequently been resulting conflicts or tensions. Using conflict and integration approach, therefore, this article observes the dynamics relation between ethnic groups, Madura and Dayak ethnic in particular, in certain plural regions in term of ethnic diversities; those are Yogyakarta, Malang and Sampit. After describing an extensive theoretical description, the writers proposed hypothesis and then analyze them quantitatively. Such hypothesis consist of the different integration quality between both Dayak and Madura ethnic groups; the different integration quality between Muslim and Christians; the different integration quality between majority and minority groups; the positive correlation between educational level of people and the integration quality; and the negative correlation between social- economic status and the integration quality, etc. In short, the empirical data perform that religious variables have a crucial role in determining the quality of conflict and integration in term of the relation between both Dayak and Madura ethnic.